Breeding for resistance of Triticum aestivum L. against Zymoseptoria tritici (Desm.) in the conditions of the Central Forest-Steppe of Ukraine - Khoroshko, N.; Lisova, H. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To analyze the starting material of soft winter wheat for resistance against Zymoseptoria tritici Rob. et. Desm. and to select resistant samples, to monitor the manifestation of the resistance trait in intervarietal F1 hybrids. Methods. Field, immunological, analytical. Results. In 2023—2025, 31 varieties of soft winter wheat were tested for resistance to Z. tritici on a natural and artificial infectious background with enhanced virulence. In 2023, the varieties Ekpromt and Zolotokolosa were resistant to Z. tritici. In 2024, 6 samples of MIP Knyazhnya, Ekpromt, MIP Yuvileyna, Zolotokolosa, Pokrovskaya and Vagoma were resistant. In 2025, the intensity of the lesion was 5.0%, MIP Yuvileyna — very high resistance 0.1—5.0%. Resistance of 5.1—10.0% was observed in 9 varieties of MIP Knyazhnya, Avrora Mironivska, Zysk, Kubok, Lira Odesa, Spadshchyna Odesa, Pontiyka, Zhuravka Odesa, Mudrisht Odesa. In 2023—2025, different intensities of damage to Z. tritici varieties were detected. Resistance was demonstrated by the varieties of MIP Knyazhnya and MIP Yuvileyna. Moderate resistance of 10.1—15.0% was determined in 6 varieties: Aurora Mironivska, Zolotokolosa, Ekpromt, Pokrovska, Optima Odesa and Vagoma. Analysis of intervarietal F1 hybrids in 2024 showed a different nature of inheritance of resistance to Z. tritici — from positive overdominance (heterosis) to negative overdominance (depression). Depression was detected in 9 hybrids. Partial negative inheritance was identified in 10 cross combinations. In 2025, depression was observed in 4 hybrid combinations. 8 intervarietal cross combinations showed partial negative inheritance. Conclusions. Testing of soft winter wheat varieties on natural and artificial infectious backgrounds of the pathogen Z. tritici with a high level of virulence makes it possible to determine different levels of their resistance. The varieties and F1 hybrids identified during the research will be used in further breeding work for resistance against the pathogen Zymoseptoria tritici in the conditions of the Central Forest-Steppe of Ukraine.